Las abejas sociales: organización y comunicación - Domínguez Liévano, Alexis (2024)
It is estimated that there are approximately 35,000 species of bees worldwide, including many that do not fit our concept of a bee. Among all this diversity, social bees account for only 9.4% of species. Among the main characteristics of these bees is that they live together, collaborate and are very communicative among the members of the hive, sharing their findings and daily work activities. In this sense, with the research that has been carried out on communication in social bees, we know that they maintain an organized system, or rather divided into hierarchies, to share information accurately, and carry out important events such as mating, caring for the young, gathering food/ materials and the collective response to any danger. The study of these fascinating "forms of communication" in bees allows us to know in detail the innards of the life of social bees and to learn even more about the wonders of nature.